V2O5 / WO3 / AgI photocatalyst capable of efficiently degrading organic dye and having antibacterial activity
By constructing a V2O5/WO3/AgI heterojunction structure for the photocatalyst, the problems of poor visible light response and low antibacterial efficiency of existing photocatalytic materials were solved, achieving efficient degradation of organic dyes and antibacterial properties, demonstrating excellent photocatalytic performance and antibacterial effect.
Patent Information
- Application Number
- CN202411548537.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-07
AI Technical Summary
Existing photocatalytic materials such as TiO2 and ZnO have poor visible light response and low quantum conversion efficiency, making it difficult to meet the needs of practical applications. At the same time, traditional antibacterial methods are costly and inefficient, and there is a lack of environmentally friendly and efficient photocatalytic antibacterial materials.
By constructing a double Z-shaped heterojunction structure of V2O5/WO3/AgI, a sheet-like V2O5/WO3/AgI photocatalyst was prepared using hydrothermal and coprecipitation methods. Photogenerated holes are concentrated in the valence band of V2O5, while electrons are concentrated in the conduction band of AgI, which inhibits electron-hole recombination and improves photocatalytic performance.
It achieves efficient degradation of organic dyes and antibacterial effects under visible light. Rhodamine B has a degradation rate of 98.55% and has a significant antibacterial effect on Escherichia coli. After 60 minutes of light exposure, it is almost sterile.
Smart Images

Figure CN119259084A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of nano material preparation, environmental governance and photocatalytic antibacterial, and in particular to a V-type nanomaterial having high efficiency in degrading organic dyes and having antibacterial activity. 2 O 5 / WO 3 / AgI photocatalyst. Background Art
[0002] With the development of economy and industry, energy crisis and environmental pollution have become the main problems in the field of science and technology. Water pollution is mainly divided into three categories, including industrial water pollution, agricultural water pollution and domestic water pollution. The presence of pollutants in water that are toxic to the human body and difficult to degrade directly endangers human health and survival. Traditional sewage treatment methods are mainly divided into three categories, physical methods, chemical methods and biological methods, including adsorption, coagulation, chemical precipitation, membrane separation technology and electrochemical methods. However, they all have disadvantages such as high cost and low treatment efficiency, and are still a certain distance away from actual production and life. Photocatalysis is widely used in the degradation of organic and comprehensive wastewater due to its high catalytic activity, simple equipment, convenient operation, low energy consumption, strong oxidation ability and no secondary pollution. The process of photocatalytic degradation of dyes is actually a redox process. When energy greater than the forbidden band (Eg) is injected, the electrons inside the catalyst are excited from the valence band (VB) to the conduction band (CB), thereby generating photogenerated electrons (e - ) and holes (h + ), however, most of the e - and h + will be reassembled quickly, with only some unrecombined e - and h + Will be transferred to the surface active sites of the photocatalyst. - and h + It will react with oxygen molecules and water molecules in the dye solution to generate superoxide free radicals (·O 2 - ) and hydroxyl radicals (·OH). The generated ·O 2 - and ·OH are both active groups, which will further induce the redox reaction on the catalyst surface, thereby achieving the effect of degrading the dye. In order to inhibit and eliminate harmful bacteria around us, further research on antimicrobial agents is necessary. Waterborne bacteria / viruses pose a huge threat to human health. Although microorganisms can be inactivated by strategies such as chlorination, ozone, and ultraviolet radiation filtration. However, these technologies also show some disadvantages, such as high cost and low efficiency. There is an urgent need to establish an effective and environmentally friendly method. Since e is produced during the photocatalytic process - and h + , e - Can be used with O2 Formation O 2 - ,h + Oxidize H 2 O generates ·OH, ·O 2 - Both ·OH and ·OH are redox active species that can react with cell membranes, destroy the internal structure of bacteria, and thus kill them. Catalytic technology based on semiconductor materials can be considered as a low-cost, environmentally friendly advanced product oxidation technology. However, traditional photocatalytic materials, such as TiO 2 and ZnO, have poor visible light response, low quantum conversion efficiency, low solar energy utilization, and are difficult to meet the needs of practical applications. Therefore, the preparation of new photocatalytic materials with a wide visible light absorption range, high electron and hole separation efficiency, and environmental friendliness is of great significance in the field of photocatalytic wastewater treatment and antibacterial research.
[0003] Since the 1980s, a large number of semiconductor materials have been widely used in the degradation of pollutants and the reduction of CO 2 In the early research on semiconductor materials, people were limited to studying wide-bandgap semiconductors with strong redox ability, such as TiO 2 , ZnO, CeO 2 and SnO 2 This means that they can only undergo catalytic reactions when excited by ultraviolet light, which is very limiting. 2 O 5 ) is a typical narrow bandgap semiconductor that absorbs in the visible light range and is an efficient photocatalyst. And V 2 O 5 As a transition metal oxide, it has the advantages of rich chemical reserves, low price and high redox potential, stable chemical properties, low cost and easy preparation. It has won a place as a semiconductor photocatalyst in the field of photocatalytic degradation of organic pollutants. 2 O 5 Because of its narrow band gap, photogenerated electrons and holes are more likely to recombine in the excited state, and the stored energy is immediately consumed by carrier recombination. Therefore, it is necessary to modify it to improve the photocatalytic efficiency.
[0004] Tungsten trioxide (WO 3 ) is also an n-type semiconductor material with a relatively narrow band gap (2.4-2.9eV), which has attracted much attention due to its unique visible light response and good thermal stability. It is widely used in the photocatalytic decomposition of organic dyes under visible light irradiation. However, as a single-component photocatalyst, its conduction band edge (+0.3-0.5V NHE) is low, and there is not enough energy to improve the separation of photogenerated carriers, so the photocatalytic reaction efficiency is poor. These defects can be overcome by morphology adjustment, heterojunction construction, noble metal doping and other methods to improve the efficiency of photogenerated carrier separation. 2 O 5 and WO 3 Composite, construct heterojunction. Heterojunction can not only improve the separation ability of electrons and holes, but also has a higher redox ability, so it has received more and more attention. In this system, electrons are kept at a more negative potential, while holes are kept at a more positive potential, which can effectively promote the separation of charges and improve photocatalytic activity.
[0005] Silver iodide (AgI) is an important photosensitive material widely used in photoreactions. When AgI is dispersed on a carrier material, it has high catalytic activity and a certain stability. AgI has excellent photocatalytic activity in the photocatalytic disinfection and degradation of many organic pollutants, but its photosensitivity makes it unstable as original AgI. This is because the conduction band potential of AgI is too high, which can be reduced by combining with other semiconductors. Quantum dot co-catalysts are widely used in the field of metal oxide photocatalysts. They have excellent response to visible light, and can also improve the separation efficiency of photogenerated electrons and holes in the material, improve the transfer efficiency of photogenerated carriers, and thus promote the improvement of the photocatalytic performance of the material. Therefore, AgI can be used as a quantum dot and V 2 O 5 The AgI quantum dots have good electronic conductivity and can efficiently separate the photogenerated electron-hole pairs. Moreover, the electrons can gather in the AgI quantum dots, thereby inhibiting the recombination of electron-hole pairs, thereby improving the photocatalytic performance of the material.
[0006] V 2 O 5 As a photocatalyst, due to its narrow band gap, it can absorb visible light and has its own performance advantages. 2 O 5 The research in this field is gradually increasing, and the morphology and performance of the synthesized products are also different. 2 O 5 , WO 3 There is no report on the related work of ternary composite of WO and AgI. 3 , and the co-precipitation preparation of AgI have all been reported. However, considering these technologies comprehensively, the method of artificially designing and constructing a double Z-type heterojunction structure has not been reported. The construction of the heterojunction gathers the photogenerated holes in V 2 O 5The electrons are gathered in the conduction band of AgI quantum dots, thereby preventing the recombination of electrons and holes and further improving the photocatalytic performance. The existing reported related research and the present invention have a huge difference in performance. First of all, from the morphology of the material, this sheet V with a large specific surface area and quantum dots distributed on the surface 2 O 5 / WO 3 / AgI material has never been reported before. This structure has a higher specific surface area and more active sites, which is more conducive to further modification and assembly of guest components. Secondly, from the perspective of the material preparation method, the simple hydrothermal, calcination and co-precipitation methods can better save costs. At the same time, in the present invention, AgI quantum dots were successfully prepared by co-precipitation at room temperature, which is also a highlight of the present invention. In the process of exploring the synthesis conditions, the present invention has used other silver salts as ternary complexes, and the prepared photocatalyst performance is not as good as that of the present invention. In addition, parameters such as material dosage, hydrothermal reaction temperature, and hydrothermal time are also obtained through our repeated exploration. More importantly, the V prepared by the present invention 2 O 5 / WO 3 / AgI photocatalyst exhibits a two-dimensional flake morphology. 2 O 5 Granular WO is distributed between the layers. 3 The double Z-type heterojunction structure is formed between the AgI quantum dots with a diameter of 4-8nm, which can further improve the separation and transfer of photogenerated electrons and holes in the material, thereby promoting the photocatalytic performance of the material. The present invention designs and constructs a double Z-type heterojunction, so that the photogenerated electrons are gathered on the AgI conduction band with the highest reduction potential, and the photogenerated holes are gathered on the V band with the highest oxidation potential. 2 O 5 In the valence band, the recombination of photogenerated electrons and holes is effectively suppressed, and some photogenerated electrons and O 2 The reaction generates O 2 - , so that the degradation of dye molecules mainly occurs on the AgI surface with photogenerated electrons and superoxide radicals as degradation active groups.
[0007] Although V 2 O 5 / WO 3 There are many reports on composite materials, but there is no specific information on sheet V 2 O 5 / WO 3 There are very few reports on composite materials. The key factor for obtaining the sheet structure in the present invention is the hydrothermal synthesis of WO 3Precursors are not something that researchers in this field can easily know through experience, but rather information that can only be obtained through a large number of experiments. However, this two-dimensional structure is one of the key factors for the material prepared by the present invention to have efficient photocatalytic effect. AgI is photosensitivity, and it reacts with WO 3 The reports on the composite materials are very rare, and AgI and V 2 O 5 The binary composite material and V 2 O 5 / WO 3 There are almost no related reports on AgI / AgI ternary composite materials, not to mention that the present invention constructs AgI into a quantum dot structure, which is not something that researchers in related fields can predict.
[0008] The material composition, energy level structure and material structure obtained by the present invention are carefully designed, so as to realize a catalyst with the dual properties of dye photodegradation and antibacterial, which leads to the excellent and unique properties of the photocatalytic material prepared by the present invention. The material preparation process parameters are determined one by one after a long period of careful exploration, so the product of the present invention is novel in morphology, advanced and unique in product performance, and original in preparation method. The prepared material has extremely broad application prospects in many fields such as photocatalytic degradation of organic pollutants, photocatalytic antibacterial, gas sensitive devices, semiconductor sensors, etc. The material synthesis method explored by the present invention provides a precedent for the preparation of other composite materials and the synthesis of other semiconductor materials. Summary of the invention
[0009] The present invention prepares a V having high efficiency in degrading organic dyes and having antibacterial activity 2 O 5 / WO 3 / AgI photocatalyst, characterized in that sodium tungstate dihydrate (Na 2 WO 4 ·2H 2 O) as WO 3 WO was prepared by a simple hydrothermal method. 3 , ammonium metavanadate (NH 4 VO 3 ) as V 2 O 5 The precursor was calcined with WO 3 Combined to form a heterojunction, and then AgI quantum dots were prepared by co-precipitation. 2 O 5 / WO 3 / AgI photocatalyst presents a two-dimensional sheet structure. 2 O 5 Granular WO is distributed between the layers. 3and AgI quantum dots with a diameter of 4-8nm, artificially designed to construct a double Z-type heterojunction, and gather the photogenerated holes in V 2 O 5 The catalyst degrades Rhodamine B (RhB) by 98.55% within 16 minutes under visible light irradiation. The catalyst can also achieve photocatalytic antibacterial effect under visible light. Using Escherichia coli without catalyst as a comparison, it can be found that the catalyst has a significant antibacterial effect on Escherichia coli. After 60 minutes of visible light irradiation, almost no Escherichia coli was observed to survive in the sample with the catalyst added. The catalyst can degrade organic dyes under visible light irradiation and effectively fight bacteria.
[0010] The photocatalyst designed by the present invention is realized as follows: WO synthesized by hydrothermal method 3 As a precursor, NH 4 VO 3 As a vanadium source, WO 3 Grind and mix thoroughly, and place in a muffle furnace for calcination to obtain lamellar V 2 O 5 / WO 3 The flake morphology synthesized by this method can greatly increase the specific surface area, thereby providing more active sites. 3 AgI quantum dots are synthesized by a simple precipitation method using KI as raw materials, so that they are distributed on the sheet layer to improve the photocatalytic performance. The synthesis process of the method of the present invention is simple to operate and has high efficiency. The specific steps are as follows:
[0011] (1) Accurately weigh 0.5-5g of Na 2 WO 4 ·2H 2 O is dissolved in 30-100 mL of deionized water and stirred on a magnetic stirrer at room temperature to dissolve;
[0012] (2) Slowly add 2M HCl to adjust the pH to 1-2;
[0013] (3) The mixture was stirred at room temperature for 1 hour, and the obtained mixed solution was added to a hydrothermal kettle, filled to 2 / 3, heated in an oven at 100-180° C. for 10-24 hours, and then cooled to room temperature;
[0014] (4) The solution was filtered and the filtered product was dried in a drying oven at 60° C. for 24 h to obtain WO 3 ;
[0015] (5) Add 0.1-0.5 g of WO 3 With 1-5g NH 4 VO3 Put it into a mortar and grind it for 30 minutes to make it fully mixed. Put the mixture into a muffle furnace and calcine it at a heating rate of 2-10℃ / min for 1-10h to obtain V 2 O 5 / WO 3 ;
[0016] (6) The obtained 0.1-2g V 2 O 5 / WO 3 The catalyst was dissolved in 20-150 mL of deionized water and 0.01-0.5 g of AgNO was added. 3 , stir in the dark for 0.5-3h, and name the solution A. Take 0.01-0.5g of KI and dissolve it in 20-150mL of deionized water, stir for 0.5-3h, and name this solution B;
[0017] (7) Add solution B dropwise into solution A and stir in the dark for 1-8 hours;
[0018] (8) The obtained solution was filtered, and the filtered product was washed and placed in a drying oven, and dried at 60° C. for 24 h to obtain a double Z-shaped heterostructure V 2 O 5 / WO 3 / AgI composite photocatalyst material. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a flake V 2 O 5 / WO 3 SEM photos of / AgI ternary composite materials;
[0020] Figure 2 It is a flake V 2 O 5 / WO 3 TEM image of / AgI ternary composite material;
[0021] Figure 3 It is a flake V 2 O 5 / WO 3 XRD spectrum of / AgI ternary composite material;
[0022] Figure 4 It is a flake V 2 O 5 / WO 3 The degradation rate curve of the organic pollutant RhB photodegradation by the / AgI ternary composite material is also used as the abstract figure.
[0023] Figure 5 It is a flake V 2 O 5 / WO 3 / AgI ternary composite material photocatalytic antibacterial effect diagram, which also serves as the abstract illustration. DETAILED DESCRIPTION
[0024] The Na selected in the present invention 2 WO 4 ·2H 2 O, HCl, KI, NH 4 VO 3 , AgNO 3 , all of which were commercially available analytically pure products, and deionized water was homemade in the laboratory; the glass instruments and equipment used were commonly used in laboratories.
[0025] Example:
[0026] Weigh 2.6345 g of Na 2 WO 4 ·2H 2 O was dissolved in 50 mL of water and stirred at room temperature for 30 min to dissolve in water; then 2 M HCl solution was slowly dripped in, and pH was tested with pH test paper until the pH of the solution was about 1, and stirring was continued for 30 min. The obtained mixed solution was placed in a stainless steel hydrothermal kettle, placed in an oven and heated at 180 ° C for 18 h. After the hydrothermal kettle was cooled to room temperature, the solution was filtered, and the filtered product was washed with deionized water and anhydrous ethanol and placed in a drying oven and dried at 60 ° C for 24 h to obtain WO 3 Precursor materials.
[0027] Use an analytical balance to accurately weigh 0.2 g of the prepared WO 3 Precursor, put it in a mortar, add 2.2945g of NH 4 VO 3 , fully grind to make it evenly mixed; transfer the ground sample to a crucible, put it into a muffle furnace, set the heating and cooling rates to 5℃ / min, and calcine at 500℃ for 2h; wait for the muffle furnace to cool naturally to room temperature to obtain lamellar binary V 2 O 5 / WO 3 Composite materials.
[0028] Weigh 0.1g of V 2 O 5 / WO 3 The material was dispersed in 30 mL of deionized water and 0.0181 g of AgNO 3, stirred for 30 min in the dark, named solution A; in another beaker, add 0.0176 g of KI and dissolve it in 30 mL of deionized water, stir for 30 min, named solution B; then drop B into A, stir for 3 h in the dark, filter the obtained mixed solution, put the filtered product into a drying oven, and dry it at 60 ° C for 24 h to obtain a sheet-like ternary composite material V 2 O 5 / WO 3 / AgI.
[0029] Flake ternary V 2 O 5 / WO 3 Scanning electron microscopy images of the / AgI composite material are shown in Figure 1 As shown in the photo, it can be seen that the prepared material is composed of irregular sheet structures with a thickness of 40-50nm. This structure greatly increases the specific surface area of the prepared material and exposes a large number of active sites. Figure 2 It is a sheet-shaped ternary V 2 O 5 / WO 3 TEM image of the / AgI composite material shows that there are a large number of circular WO 3 , and at V 2 O 5 The surface of the sheet is distributed with 4-8nm AgI quantum dots; the prepared sheet-like ternary V 2 O 5 / WO 3 The X-ray diffraction analysis results of the / AgI composite materials are shown in Figure 3 As shown, by comparing with the standard card, it can be seen that the prepared material is mainly composed of V 2 O 5 , WO 3 and AgI; Figure 4 It is a sheet-shaped ternary V 2 O 5 / WO 3 The degradation rate curve of RhB degradation by using AgI composite material as catalyst. It can be seen from the figure that after the catalyst reaches the adsorption equilibrium in dark treatment, the degradation rate of RhB is as high as 98.55% within 16 minutes of illumination. Figure 5 The antibacterial effect of the ternary composite photocatalyst on Escherichia coli under visible light irradiation is shown in the figure. It can be seen from the figure that after the addition of the photocatalyst, the number of Escherichia coli is significantly reduced, and almost no Escherichia coli can be observed after 60 minutes of illumination, proving that the flake ternary V 2 O 5 / WO 3 / AgI composite materials have strong antibacterial effect. These results show that the prepared sheet-like ternary V 2 O5 / WO 3 / AgI composite materials will have great application prospects in the fields of photodegradation of pollutants and antibacterial.
[0030] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art may make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A V2O5 / WO3 / AgI photocatalyst with high efficiency in degrading organic dyes and antibacterial activity, characterized in that: The prepared V2O5 / WO3 / AgI photocatalyst presents a two-dimensional sheet structure, and its component is V2O5. Granular WO3 and AgI quantum dots with a diameter of 4-8nm are distributed between the V2O5 sheet structures, and a double Z-type heterojunction structure is formed between the three. Photogenerated electrons gather on the AgI conduction band with the highest reduction potential, and photogenerated holes gather on the V2O5 valence band with the highest oxidation potential, which effectively promotes the separation and transfer of photogenerated electrons and holes. The photocatalyst has a very efficient degradation ability for organic dyes under visible light irradiation, and the degradation rate of RhB within 16 minutes is as high as 98.55%. The catalyst can also achieve photocatalytic antibacterial under visible light, and almost no Escherichia coli survival is observed in the culture dish after 60 minutes of visible light irradiation. The preparation method of the V2O5 / WO3 / AgI photocatalyst with efficient degradation of organic dyes and antibacterial activity is as follows: (1) Preparation of two-dimensional flake V2O5 / WO3 by combining hydrothermal method and high-temperature solid phase method The prerequisite for obtaining the two-dimensional sheet structure is that WO3 prepared by hydrothermal method must be used as a precursor. The specific preparation process is as follows: Accurately weigh 0.5-5g of Na2WO4·2H2O and dissolve it in 30-100mL of deionized water. Stir it under magnetic force at room temperature until it is completely dissolved. Slowly drip 2M HCl to adjust the pH to weak acidity. Continue stirring at room temperature for 1h, transfer the obtained mixed solution to a hydrothermal reactor, perform hydrothermal reaction at 100-180℃ for 10-24h, cool it to room temperature, filter and wash the solid product, and dry it at 60℃ for 24h to obtain a WO3 precursor. Take 0.1-0.5g of the WO3 precursor and 1-5g of NH4VO3 and put them into a mortar and grind them for 30min. Put the mixture into a muffle furnace and calcine it at 500℃ for 1-10h at a heating rate of 2-10℃ / min to obtain a two-dimensional sheet V2O5 / WO3. (2) Synthesis of double Z-shaped two-dimensional flake V2O5 / WO3 / AgI composite photocatalyst The present invention distributes AgI quantum dots on two-dimensional flake V2O5 / WO3 by a simple coprecipitation method, and the presence of AgI quantum dots is a necessary condition for constructing a double Z-type heterojunction. The specific preparation process is as follows: Accurately weigh 0.1-2g of V2O5 / WO3 and disperse it in 20-150mL of deionized water, add 0.01-0.5g of AgNO3, stir in a dark room for 0.5-3h, and name the resulting solution dispersion A. Accurately weigh 0.01-0.5g of KI and dissolve it in 20-150mL of deionized water, stir for 0.5-3h, and name this solution solution B. Under magnetic stirring, add solution B dropwise into dispersion A, stir in a dark room for 1-8h, filter the product, wash with deionized water, and dry at 60°C for 24h to obtain a V2O5 / WO3 / AgI composite photocatalytic material with a double Z-type heterostructure.